Repeat peritonitis in peritoneal dialysis : A cohort study - Nabil Hmaidouch; Sara El Maakoul; Hajar Fitah; Naima Ouzeddoun; Loubna Benamar (RDPLF, 2024)
Introduction: The understanding of the pathophysiological mechanisms of repeat peritonitis, defined as the occurrence of peritonitis more than 4 weeks after the end of appropriate antibiotic treatment for a previous episode involving the same germ, remains limited. Methods: We studied the outcomes of 26 episodes of repeat peritonitis between 2006 and 2024 (Repeat Group) and compared them with 23 episodes of relapsing peritonitis (Relapse Group) and 84 episodes of peritonitis preceded by 4 weeks or more by another episode with a different organism (Control Group). Results: The majority of cases of repeat peritonitis are caused by gram-positive organisms (65.5%), predominantly Staphylococcus aureus (38.5%), whereas most episodes of relapsing peritonitis are culture-negative (69.5%), followed by gram-negative bacilli episodes (17.4%). Exit site infection is significantly associated with PD peritonitis. Gram-positive cocci are responsible for 95.5% of exit site infections, mainly due to Staphylococcus aureus. In the Repeat Group, 14 (66%) patients achieved primary response, and 10 (47%) of them reached complete cure. After the first episode of repeat peritonitis, 3 (14%) patients had their catheter removed and were transferred to long-term hemodialysis. ; however, the risk of developing relapsing peritonitis was 4.7%, and recurrent peritonitis was 9.5%. Conclusion: The definition of repeat peritonitis is clear. Despite a favorable outcome with antibiotic treatment, the risk of further episodes of peritonitis remains high, threatening the time on peritoneal dialysis therapy and the life of the patient.